Concept of Disaster is in Disarray: Need a Consensus among Experts - Amarasinghe, A.G (International Journal of Geography and Geology, 2020)
Huge number of definitions is in use national and international spheres to provide a meaning for the concept of “disaster”. Most of them are defined vaguely and others inclined to limited aspects. Concept of disaster with different meanings causes to socialize different understandings on the nature of disaster. This background leads to interpret and make plans for disaster management program from various points of views. Reaching the objective of disaster management program depends entirely on the consensus of the “concept of disaster”. Consensus helps groups to work together to meet the group’s objectives. Therefore, adhering to a consensus and unanimous concept of disaster can be regarded as the main solutions to solve array of problems related disaster management programs. Aim of this study is to identify the disagreement nature of the concept of disaster and the negative impacts of it. Qualitative data are main type of data used in this study. Reviewing literature through web page browsing was the main method used to collect data. The results of this study reveal that absence unanimously agreed concept of disaster has created a meaning crisis of the concept of disaster. This background led to practice disaster management program among respective authority without any consensus which end without successful results. One of the main reason for this is imperfect concept has led to formulate disaster management programs paying way to neglect, ignore and abandon well established disaster management policies, legal systems, institutions and its networks, reserved human and other capitals.